2013
DOI: 10.2174/1566523211313020002
|View full text |Cite
|
Sign up to set email alerts
|

Technological Overview of iPS Induction from Human Adult Somatic Cells

Abstract: The unlimited proliferation capacity of embryonic stem cells (ESCs) combined with their pluripotent differentiation potential in various lineages raised great interest in both the scientific community and the public at large with hope for future prospects of regenerative medicine. However, since ESCs are derived from human embryos, their use is associated with significant ethical issues preventing broad studies and therapeutic applications. To get around this bottleneck, Takahashi and Yamanaka have recently ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 198 publications
(265 reference statements)
0
74
0
5
Order By: Relevance
“…However, the retro-virally reprogrammed cells produced more robust HIO epithelial cell marker expression and this may be relevant for their use as translational 3D models of the gut physiology and pathophysiology. While retrovirally reprogrammed cell lines have been essential for the initial characterization of iPSCs relative to embryonic stem cell lines, they are incompatible with therapeutic applications, as genomic integration of reprogramming factors introduces a risk of insertional mutation that can potentially disrupt cellular stability and function [19]. High expression of pluripotent markers was evident in E2055A, which showed deviations from ideal ESlike morphology within maintenance cultures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the retro-virally reprogrammed cells produced more robust HIO epithelial cell marker expression and this may be relevant for their use as translational 3D models of the gut physiology and pathophysiology. While retrovirally reprogrammed cell lines have been essential for the initial characterization of iPSCs relative to embryonic stem cell lines, they are incompatible with therapeutic applications, as genomic integration of reprogramming factors introduces a risk of insertional mutation that can potentially disrupt cellular stability and function [19]. High expression of pluripotent markers was evident in E2055A, which showed deviations from ideal ESlike morphology within maintenance cultures.…”
Section: Discussionmentioning
confidence: 99%
“…These two observations suggested to us that changes in handling and localization of structures, could drive the outcome to successful differentiated HIO, maybe as much as the differentiation growth factor protocols. Finally, iPSC lines can be produced by the forced expression of reprogramming transcription factors (e.g., Oct4, Sox2, Klf4, and c-Myc) by means of retroviral transduction [1] although this can potentially disrupt cellular stability and function [19]. Thus, to compare the robustness of intestinal differentiation, five cell lines were contemporaneously differentiated and their morphology and a number of markers of differentiation through HIO tracked.…”
Section: Introductionmentioning
confidence: 99%
“…Reprogramming efficiency (i.e., the number of starting somatic cells which transition to hiPSCs) has been reported to be significantly enhanced by addition of supplementary pluripotency factors (12) or epigenetic modifiers (160) to the reprogramming mix. Rais et al (225) and Lujan et al (168) also demonstrated in both human and mouse cells that almost 100% of cells in a differentiated population are capable of reprogramming following depletion of Mbd3, a core member of the Mbd3/NuRD (nucleosome remodeling and deacetylation) repressor complex.…”
Section: Tools For Reprograming Somatic Cells To Hipscsmentioning
confidence: 99%
“…iPS cells are obtained by the reprogramming of body somatic cells with some gene transcription factors. They were first produced from mice dermal fibroblast cells by the retroviral gene transfer method with Oct3/4, Sox2, Klf4, and cMyc (OSKM) factors, also known as the Yamanaka factors (Figure) (Takahashi and Yamanaka, 2006;Bayart and Cohen-Haguenauer, 2013). iPS cells were obtained from human dermal fibroblasts a year later by the same authors (Takahashi et al, 2007).…”
Section: Ips Cellsmentioning
confidence: 99%